Representing Spaces, Performing Places: le strade di Londra nel romanzo Absolute Beginners (1958) di Colin MacInnes e nella sua versione cinematografica (Altre Modernità, 2019)
This paper addresses life in London in the late 1950s portrayed by the musical film Absolute Beginners (1986) directed by Julien Temple and its fictional source, that is Colin MacInnes’ novel of the same name (1958). While the musical film has been criticized for its lack of character development and for its last-minute attack on racism, MacInnes’ Absolute Beginners was a successful novel. It tells the story about youth subcultures in postwar London and in this paper I will examine the way in which the City of London and its transformation is portrayed as a urban space/place where young people create and establish new places and spaces for themselves for their regular encounters. So, London as the setting becomes not just a background element but a driving force in the whole story. By seeking to understand London as a site of local encounter, global exchange, national significance, and social memory this paper aims at providing an analysis of the places and spaces both of the film musical and the novel which characters absorb the audience/reader and show the variety of human experience of the capital as seen through the eyes (and camera lens) of a nameless 18 year-old photographer.